The promises and pitfalls of ecosystem-based adaptation to climate change as a vehicle for social empowerment - Stephen Woroniecki; Christine Wamsler; Emily Boyd (Ecology and Society, 2019)
Ecosystem-based adaptation (EbA) to climate change is an approach claimed to deliver social benefits relevant to marginalized groups. Based on a structured literature review, we interrogate such claims, asking whether such approaches may (or may not) contribute to social change and, more specifically, empowerment. We present a review of the predominant meaning and interlinkages of the EbA and empowerment concepts, which shows that EbA pays insufficient attention to issues of empowerment and agency. On this basis, we discuss how an empowerment lens could be (better) integrated into the conceptualization of EbA, suggesting key dimensions through which this could be supported. We show that the emphasis on empowerment theory and the merits that it brings to the EbA literature are helpful, leading to a number of important questions to adaptation projects on the ground. Incorporating an empowerment lens leads to an increased consideration of issues of power more broadly, especially the way marginalized groups' agency, access, and aspirations are conditioned by social structures that may prevent strategic adaptation choices. We conclude that EbA will facilitate empowerment better by explicitly considering how social benefits can emerge from the interplay between particular types of actions, marginalized people's adaptive strategies, and their relational context.